1. The problem statement, all variables and given/known data z = 2y^2 - x^2 2. Relevant equations 3. The attempt at a solution I kind of know how to do it. z = y^2/b^2 - x^2/a^2 the first power is the axis of paraboloid. let x = k thus z = 2y^2 - k^2 and the vertex of this parabola (if x = 0 we see it is a parabola), v = (k, 0, -k^2) if now x = k, the vertex becomes v = (0,0,0) so far, do you guys agree? similarly, for y = k v = (0,k, 2y^2) and when y = 0, we have v = (0,0,0) and for z = k, we find z = k = 2y^2 - x^2 gives us a hyperbola.